Education as Socio-cultural and Economic Potential of the Global Information Society - Taranenko, Natalia Yurievna; Rusetskiy, Mikhail Gennad’evich; Yanova, Elena Alekseevna; Okorokova, Olga Alekseevna; Aygumov, Timur Gadzhievich (Journal of History Culture and Art Research, 2019)
The article deals with education as socio-cultural and economic potential of the global information society affecting its development directly. Education alongside society is in a situation of development, self-development and evolution. In the context of the given problem this development and the factors affecting it mostly are considered. Modern education is changing its purpose, transforming from social and state institution to a universal means of cultural transformations. Therefore, in the modern world, the importance of education as the most important factor in the formation of new quality not only of culture, but also of society as a whole, is increasing. The issues of humans’ spirituality and their value orientations are becoming of particular importance. The change in the value of modern education fundamentally modifies the outlook on educational activities and leads to changes in the modern education system, including the Russian one.